On Hausdorff compactifications of non-locally compact spaces - James Hatzenbuhler; Don A. Mattson (International Journal of Mathematics and Mathematical Sciences)
Let X be a completely regular, Hausdorff space and let R be the set of points in X which do not possess compact neighborhoods. Assume R is compact. If X has a compactification with a countable remainder, then so does the quotient X/R, and a countable compactificatlon of X/R implies one for X−R. A characterization of when X/R has a compactification with a countable remainder is obtained. Examples show that the above implications cannot be reversed.